A double blinded trial to compare the patient satisfaction and crown accuracy of two different intraoral scanners for the fabrication of monolithic lithium disilicate single crowns - Chun-Hsiu Yang; Chih-Wen Cheng; Sung-Ying Ye; Chia-Hui Chien (Elsevier, 2023)
Background/Purpose: The digital impression is a promising technique in prosthodontic treatment. However, the influencing factors of patient comfort is lacking, and the evidence of crown quality is mostly based on in vitro studies. The purpose of this double-blinded clinical trial was to compare the patient satisfaction and crown accuracy of two different intraoral scanners (IOSs) for the fabrication of all-ceramic single crowns (SCs). Materials and methods: Participants in need of posterior tooth-supported SCs were enrolled. Each patient received quadrant scan by both the Metal Industries Research and Development Centre (MIRDC) IOS and Carestream CS3500 in a random sequence. After scanning, participants had to fill in a 6-item perception questionnaire that based on 5-point Likert scale for two IOSs. Both data were sent to a dental laboratory to fabricate the monolithic lithium disilicate SCs. The crown accuracy including marginal fit, proximal contact, occlusal contact, and general satisfaction were accessed based on 5-point scale. Results: A total of 15 participants with 40 crowns (20 SCs in each group) were investigated. Regarding to patient satisfaction, there was no statistically significant difference in total score between MIRDC and Carestream IOSs (23.6 ± 3.79 vs 23.1 ± 4.28, P = 0.36). In terms of crown accuracy, there was significantly different in total score and all the evaluated parameters between MIRDC and Carestream groups (6.1 ± 1.41 vs 13.3 ± 3.75, P < 0.001). Conclusion: Both MIRDC and Carestream IOSs can provide good patient satisfaction during intraoral scanning. The Carestream IOS obtains better accuracy for the fabrication of all-ceramic SCs.